Odisha revisited: a personal account - Serjeant, Graham R.; Kulozik, Andreas; Serjeant, Beryl E. (Frontiers in medicine, 2021)
In 1986, a paper in the Lancet was the first to collate hematology, molecular findings, and clinical features of homozygous sickle cell (SS) disease in India. The paper came from the group organized by Professor Bimal Kar in Burla Medical College, Sambalpur University, in western Odisha. Although widely quoted, few readers will be aware of the history of this work that is now attached in an informal summary.
Gesehen am 14.12.2021